Tectonic significance of the sedimentary and palaeocurrent record at the eastern edge of the Karoo Basin. (October 2019) - Hastie, Warwick W.; Watkeys, Michael K.; Smith, Alan M.
Abstract: The Permian-aged coal-bearing Vryheid Formation is the central stratigraphic unit of the Ecca Group within the Karoo Supergroup. In the main Vryheid Formation basin the succession comprises upward coarsening deltaic fan sediments followed by upward fining fluvial sequences. A narrow belt of the Vryheid Formation crops out along the KwaZulu-Natal (KZN) north coast, approximately ∼200 km south of the main Vryheid depocentre. The outcrops consist mainly of cliffs and rugged terrain in which predominantly fluvio-deltaic sedimentary sequences occur, along with highly carbonaceous and lower delta front sediments. Interpretation of detailed sedimentary logs suggests northward deepening of the succession, along with southerly-directed palaeocurrents in the shallower, coarse-grained and immature sediments. Broadly northerly-directed palaeocurrents are recorded in the lower delta front sediments. While the sedimentary record in this area might be discounted as merely a distal portion of the main Vryheid Formation basin, we contend that there is inconsistency relative to the main basin, and that there is a linked history in the pre-, syn- and post-Ecca depositional record. The syn-Ecca record we present from the eastern margin of the Vryheid basin, along with pre- and post-Ecca records and an appraisal of the incumbent tectonics, suggests that there was a relatively persistent control on sediment sourcing which existed to the southeast of the current KZN coastline. This region was most likely an uplifted area of the Maurice-Ewing Bank, which lay immediately offshore of what is now the KZN coast in a tight refit between Antarctica and Africa. Highlights: The Vryheid Formation along the east coast of South Africa comprises deltaic and fluvial sequences. Coarse-grained, immature sediments were derived from the north, delta front deposits from the south. Southerly sediment source and northward deepening of delta front deposits conflicts with main Vryheid Basin. Synthesis of literature reveals continental assembly likely controlled local depositional setting.